Technological productions developed by Nursing: systematic review (Research, Society and Development, 2020)
Objective: To analyze, through the systematic review method, the technological products developed by Nurses, published between 2014 and 2018. Methodology: Qualitative systematic review of articles published from 2014 to 2018 in English, Portuguese and Spanish. Technological productions focused on the hospital environment were listed. Technological production was classified according to: complexity, innovation content, impact and applicability based on the criteria determined by the Coordination of Superior Level Staff Improvement (Brazil). Results: 28 studies were selected. The most frequent technological productions were: manual/protocol and software/application (28.57%, respectively), teaching material (25%) and non-patentable process/technology (17.86%). There was a greater distribution of technological productions classified as medium complexity (78.6%); medium content of innovation (57.1%); the description of the impact was recurrent in software/application (60%), didactic material and non-patentable process/technology (12.5%, respectively) and, regarding the manual/protocol, the impact was not reported by the authors. The applicability was not clear in the studies, being interpreted from the profile of the production presented. Conclusion: There were more frequent technological productions of manuals/protocols and software/applications. There is a lack of description as to the applicability and impact (real or potential) of productions aimed at the hospital environment.